FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA CAKUPAN PEMBERIAN IMUNISASI TETANUS TOXOID (TT) CALON PENGANTINDI WILAYAH KERJA PUSKESMAS KURAI TAJI KOTA PARIAMAN TAHUN 2020 - Rika Aramlini (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2022)
TT immunization is a tetanus germ vaccine that has been weakened. This TT immunization is an activeartificial immunization by giving the complete Tetanus Toxoid vaccine which is expected to preventTetanus Neonatorum with >90% protection. In developing countries, most of the causes of neonatal deathare tanus neonaturum kanena, which are born in unclean and non-sterile places. The purpose of this studywas to determine the factors associated with the low coverage of tetanus toxoid (TT) immunization forprospective brides in the Working Area of the Kurai Taji Health Center in 2020. The research wasconducted in April 2020. This type of research was an analytical descriptive study with a cross sectionaldesign. The population in this study were all prospective brides/WUS in the working area of the KuraiTaji Health Center in 2020 as many as 1806 WUS, using a random sampling technique to obtain a sampleof 30 WUS. The data were analyzed univariately and bivariately using a computerized statistical testusing SPSS Ver.17 with a significance limit of α = 0.05 and a 95% degree of confidence. The results ofthe univariate analysis showed that 56.7% of the prospective brides had high knowledge, 53.3% had anegative attitude, 56.7% had low interest and 56.7% incomplete TT immunization coverage. Bivariateanalysis found a p value (p<0.05) meaning that there was a significant relationship between knowledge(p=0.002), attitude (p=0.011) and interest (p=0.033) with the coverage of TT immunization in theworking area of the Kurai Taji Health Center. 2020. It is recommended that health workers at the KuraiTaji Health Center be able to increase counseling and outreach about the importance of TT immunizationto prospective brides/mothers to prevent tetanus in the future and motivate them to continue to receivecomplete TT immunization.